Sensorimotor rhythm neurofeedback training and auditory perception - Stanković, Ivana; Ilić, Nela V.; Ilić, Tihomir V.; Jeličić, Ljiljana; Sovilj, Mirjana; Martić, Vesna; Punišić, Silvana; Stokić, Miodrag (Vojnosanitetski pregled, 2023)
Background/Aim. In everyday communication, people are exposed to a myriad of sounds that need to be sorted and relevant information extracted. The ability of a person to concentrate on certain sounds in a noisy background environment, perform selective attention, and focus their auditory attention is crucial for everyday functioning and communication. The aim of this study was to investigate the effect of the sensorimotor rhythm (SMR) (12–15 Hz) neurofeedback (NFB) training to improve auditory cognition measured by the achievements in the Quick speech-in-noise (QuickSIN) test, changes in the amplitudes and latencies of components of auditory evoked potentials (AEP) N100, N200, and P300 in the auditory oddball discrimination task, and changes in the spectral power of the SMR. Methods. The study included 16 healthy participants aged 25–40 years (8 males and 8 females). Each participant had 20 daily sessions of SMR NFB training. Auditory cognitive functions and electrophysiological correlates of cognitive processing were recorded 5 times – before NFB, after 5, 10, and 20 sessions, and one month after the last session of NFB. Results. The results showed a statistically significant decrease in N200 and P300 latencies at frontal midline (Fz), central midline (Cz), and parietal midline (Pz) regions, an improvement on the QuickSIN test, and an increase in electroencephalogram SMR rhythm spectral power in the Cz region as a result of the NFB SMR training. No significant effect of the NFB training on the N100, N200, and P300 amplitudes on Fz, Cz, and Pz was found. Conclusion. The obtained results suggest that SMR NFB affects auditory perception in terms of shorter latencies of AEP and better performance on the QuickSIN test.
Keywords: auditory perception; cognition; electroencephalography; event-related potentials, p300; evoked potentials, auditory; feedback, sensory